2022
DOI: 10.1101/2022.02.08.479592
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sub-10 nm fluorescence imaging

Abstract: Advances in superresolution microscopy demonstrated single-molecule localization precisions of a few nanometers. However, translation of such high localization precisions into sub-10 nm spatial resolution in biological samples remains challenging. Here, we show that resonance energy transfer between fluorophores separated by less than 10 nm results in accelerated fluorescence blinking and consequently lower localization probabilities impeding sub-10 nm fluorescence imaging. We demonstrate that time-resolved fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…SMLM) are negatively affected by the water environment. In contrast, technologies relying on fluorophore fluctuations profit from the expansion, as the fluorophores are spatially separated and can fluctuate independently 13 . b , Repeated imaging is performed (up to 3000 images), in any desired imaging system (confocal, epifluorescence, etc.…”
Section: Extended Data Figure Legendsmentioning
confidence: 99%
See 1 more Smart Citation
“…SMLM) are negatively affected by the water environment. In contrast, technologies relying on fluorophore fluctuations profit from the expansion, as the fluorophores are spatially separated and can fluctuate independently 13 . b , Repeated imaging is performed (up to 3000 images), in any desired imaging system (confocal, epifluorescence, etc.…”
Section: Extended Data Figure Legendsmentioning
confidence: 99%
“…First, the achievable structural resolution is determined by the labeling density, which is limited by the size of the fluorescent probes (typically 1 nanometer or larger) 12 . Second, fluorophores can interact via energy transfer at distances below 10 nm, which results in accelerated photoswitching (blinking) and photobleaching, and thus in substantially lower localization probabilities 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on fluorescently labeled DNA origami structures have shown to what degree some identical fluorophores interact when separated by distances ranging from 1 to 10 nm, leading to unique antibunching characteristics, improved photostability, and increased photoblinking . The statistical signatures of these phenomena have very recently been proposed as a tool to determine molecular distances below 10 nm . Furthermore, such experiments provide building blocks that may help in constructing models of interacting fluorophores.…”
Section: Introductionmentioning
confidence: 99%
“…40 The statistical signatures of these phenomena have very recently been proposed as a tool to determine molecular distances below 10 nm. 42 Furthermore, such experiments provide building blocks that may help in constructing models of interacting fluorophores. While antibunching experiments analyze interphoton arrival times, in this paper, we specifically investigate the effects of interactions on excited state lifetimes and excitation probabilities.…”
Section: ■ Introductionmentioning
confidence: 99%